PERAN DIREKTORAT JENDERAL BEA DAN CUKAI DALAM PENANGGULANGAN PENYELUNDUPAN NARKOTIKA JALUR LAUT DI KEPULAUAN RIAU - Rahel Kartika; Parningotan Malau (Yurisprudentia: Jurnal Hukum Ekonomi, 2021)
The crime of smuggling narcotics in the sea route is a crime that continues to increase every year. One of the government's efforts to tackle the smuggling of narcotics by sea is through the Directorate General of Customs and Excise (DJBC). This paper aims to explain how the role of DGCE marine surveillance in the prevention and control of narcotics smuggling by sea and to find out what obstacles the Directorate General of Customs and Excise has faced so that the data on prosecution for the last five (5) years has increased. This paper uses supervisory theory and criminal law policy theory to explain how the DJBC marine surveillance system and prevention efforts before and after the crime of narcotics smuggling by sea. The results of the analysis show that the DGCE marine surveillance system has a strategic function in reducing the opportunities for narcotics smuggling by sea. However, there are several obstacles to the DJBC marine surveillance system in preventing and overcoming the smuggling of narcotics by sea.